Generation and identification of anti‐inflammatory peptides from bovine β‐casein using enzyme preparations from cod and hog. (23rd April 2015) - Altmann, Karina; Wutkowski, Adam; Klempt, Martin; Clawin‐Rädecker, Ingrid; Meisel, Hans; Lorenzen, Peter Chr
Abstract: BACKGROUND: The aim of the present study was to generate and identify potential anti‐inflammatory peptides from bovine β‐casein with enzyme preparations from cod and hog. Furthermore, the potential of cod trypsin, derived from fishery by‐products, to produce these bioactive peptides for replacement of non‐food‐grade tosyl phenylalanyl chloromethyl ketone (TPCK)‐treated porcine trypsin enzyme preparation was evaluated. RESULTS: Potential anti‐inflammatory peptides were obtained by hydrolysis of β‐casein with the tryptic enzyme preparations cod trypsin, porcine trypsin (TPCK‐treated) and a porcine trypsin and chymotrypsin preparation (PTN 6.0 S). Proteolysates generated with enzyme preparations containing mainly chymotryptic activity (Cryotin, Cryotin F) did not exhibit any effect. CONCLUSION: The more chymotryptic enzyme activity is present, the lower is the potential anti‐inflammatory activity of the hydrolysates in HEK nfκb ‐ RE cells. Comparable peptides were produced by application of porcine trypsin (TPCK) and cod trypsin. Therefore, the enzyme preparation cod trypsin can replace the non‐food‐grade porcine enzyme preparation trypsin (TPCK) for the generation of potential anti‐inflammatory peptides from β‐casein. © 2015 Society of Chemical Industry